2011
DOI: 10.1590/s0102-311x2011001300004
|View full text |Cite
|
Sign up to set email alerts
|

Sex inequalities in HIV-related practices in the Brazilian population aged 15 to 64 years old, 2008

Abstract: The objective of this study is to analyze gender differences in HIV-related practices in the Brazilian population. A national survey was carried out in 2008 with a sample size of 8,000 individuals aged 15-64 years old. The sampling was stratified by macro geographical region and urban/rural areas. Logistic regression models were used to investigate the main predictors of consistent condom use. The results showed that women have less sexy, start sexual life later than men, have fewer casual sexual partners, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 28 publications
0
17
1
7
Order By: Relevance
“…24 Of note, reported condom use in this sample of truckers is quite similar to that among 15e64-year-old men participating in the recent 2008 national knowledge, attitudes and practices survey. 25 However, truckers in this study and others 7 26 27 reported multiple partners at a rate higher than the general male population.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…24 Of note, reported condom use in this sample of truckers is quite similar to that among 15e64-year-old men participating in the recent 2008 national knowledge, attitudes and practices survey. 25 However, truckers in this study and others 7 26 27 reported multiple partners at a rate higher than the general male population.…”
Section: Discussioncontrasting
confidence: 53%
“…Despite the low percentage of truckers in our study reporting sex with men (6.7%), such practices are likely not uncommon, as services of male/transvestite sex workers may be highly available along truck routes and cost less than sex with female sex workers. 25 34 The association of HSV-2 with age and inability to report one's number of lifetime partners likely reflect the truckers' time of risk exposure. No measures of sexual behaviour in the last 6 months were independently associated with HSV-2 infection; because HSV-2 is a chronic infection, lifetime measures of sexual behaviour more accurately represent one's exposure than recent report of sexual behaviour.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 40 papers 8,9,11,[17][18][19][20][21] (Table 1) and 3 DDAHV reports were included in this article to describe the production of knowledge about the use of condoms in Brazil and associated factors. The reports were not included in Table 1, but condom use information from the PCAP report 14 , the national study of crack users 12 , and the RDS-TS study 22 were described.…”
Section: Resultsmentioning
confidence: 99%
“…We also included documents from national surveys that guide the epidemiological and behavioral surveillance of the DDAHV, and included condom use as one of the main outcomes, such as in the "Sexual Behavior and Perceptions of the Brazilian Population on HIV/AIDS" survey conducted in 1998 and 2005, in a representative sample of the population aged 16 -65 years, by the Brazilian Center for Analysis and Planning (CEBRAP) 17 ; and in on the knowledge, attitudes, and practices related to STD and AIDS (PCAP), household survey undertaken in 2004 and 2008 among a representative sample of the population aged 15-64 years 14,18,19 , surveys among conscripts of the Brazilian Army 8,20 , and behavioral surveillance surveys among key populations 9,12,21,22 .…”
Section: Methodsmentioning
confidence: 99%
“…Women's lack of sexual autonomy reveals itself in the dynamics of interpersonal relationships and in health service practices, whereby these services are not always trained to provide means by which women can enjoy their sexuality while minimizing risks. 27,28 As injecting drug use has decreased, a gradual reduction in this HIV transmission route is expected. However, among blood-borne transmission, transmission due to drug use (3.4%) was most frequent.…”
Section: Discussionmentioning
confidence: 99%